Volt-per-Ångstrom terahertz fields from X-ray free-electron lasers - Tanikawa, T. (J Synchrotron Radiat, 2020)
The electron linear accelerators driving modern X-ray free-electron lasers can emit intense, tunable, quasi-monochromatic terahertz (THz) transients with peak electric fields of V Å(−1) and peak magnetic fields in excess of 10 T when a purpose-built, compact, superconducting THz undulator is implemented. New research avenues such as X-ray movies of THz-driven mode-selective chemistry come into reach by making dual use of the ultra-short GeV electron bunches, possible by a rather minor extension of the infrastructure.